Corporate Governance Mechanisms and Financial Reporting Quality of Nepalese Commercial Banks - Gomdem, Sushma Tamang; Choudhari, Sushmita; Koirala, Susmita; Acharya, Usha; Ojha, Yubraj; Pradhan, Sumit (Nepalese Journal of Business, 2024)
The study examines the effect of corporate governance mechanism on financial reporting quality of Nepalese commercial banks. Audit delay and accruals are selected as the dependent variables. Likewise, board size, audit committee, foreign ownership, board independence, number of board meeting and female board director are selected as the independent variables. The study is based on secondary data of 17 commercial banks with 101 observations for the study period from 2016/17 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual report of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance mechanisms on financial reporting quality in the context of Nepalese commercial banks. The study showed that board size has a negative impact on audit delay and accruals. It means that increase in board size leads to decrease in audit delay and accruals. Similarly, female board member has a negative impact on audit delay and accruals. It means that increase in gender board diversity leads to decrease in audit delay and accruals. Moreover, number of independent directors has a negative impact on audit delay and accruals. It shows that increase in number of independent directors leads to decrease in audit delay and accruals. Furthermore, audit committee has a negative impact on audit delay and accruals. It indicates that increase in audit committee size leads to decrease in audit delay and accruals. Likewise, number of board meetings, lower would be the audit delay and accruals. In addition, foreign ownership has a positive impact on audit delay and accruals. It shows that higher the proportion of foreign ownership, higher would be the audit delay and accruals.